Diameter Growth of Straw Mushroom (Volvariella Volvacea (Bull.) Fries) in Combination of Straw and Spent Coffee Grounds - Irfa Masyura; Samingan Samingan; Wiwit Artika; Devi Syafrianti; Wardiah Wardiah (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2020)
Substrate of straw mushroom in general are straw. Spent coffee grounds are one of the wastes that can be used as an alternative substrate for straw mushrooms. The purpose of the research are to know the diameter growth effect of straw mushrooms on spent coffee grounds substrate, as well as to know the optimal comparison of substrate combinastions for diameter growth of staw mushrooms. This research is experimental with a quantitative approach. The design used was a Nonfactorial Completely Randomized Design consisting of 5 treatments and 5 replications. The treatments were 100% straw (P0) as positive control, 75% straw and 25% spent coffee grounds (P1), 50% straw and 50% spent coffee grounds (P2), 25% straw and 75% spent coffee grounds (P3), and 100% spent coffee grounds (P4). Data were analyzed by Analysis of Variants (ANAVA) and conducted further tests by Tukey’s honestly significance difference (HSD). The results of this research indicate the substrate combination of straw and spent coffee grounds effects the diameter growth of straw mushrooms. The optimal substrate combination of straw mushrooms are P1 treatment with a combination of 75% straw and 25% spent coffee grounds.Keywords: straw mushroom, straw, spent coffee grounds, growth, diameter.Media jamur merang pada umumnya adalah jerami. Ampas kopi merupakan salah satu limbah yang dapat dijadikan alternatif media tanam jamur merang. Penelitian ini bertujuan untuk mengetahui pengaruh pertumbuhan diameter jamur merang pada media tanam ampas kopi, serta untuk mengetahui perbandingan kombinasi media tanam yang optimal bagi pertumbuhan diameter jamur merang. Jenis penelitian ini adalah eksperimental dengan pendekatan kuantitatif. Rancangan yang digunakan adalah Rancangan Acak Lengkap Nonfaktorial yang terdiri dari 5 perlakuan dan 5 ulangan. Perlakuan yang dimaksud adalah 100% jerami (P0) sebagai kontrol positif, 75% jerami dan 25% ampas kopi (P1), 50% jerami dan 50% ampas kopi (P2), 25% jerami dan 75% ampas kopi (P3), serta 100% ampas kopi (P4). Data dianalisis menggunakan Analisis Varian (ANAVA) dan dilakukan uji lanjut berupa Beda Nyata Jujur (BNJ). Hasil penelitian ini menunjukkan kombinasi media tanam jerami dan ampas kopi berpengaruh terhadap pertumbuhan diameter jamur merang. Kombinasi media tanam jamur merang yang optimal adalah perlakuan P1 dengan kombinasi 75% jerami dan 25% ampas kopi.Kata-kata kunci: Jamur Merang, Jerami, Ampas Kopi, Pertumbuhan, Diameter.